EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN TEKNIK ROLE PLAYING DALAM MENINGKATKAN INTERAKSI SOSIAL SISWA - Andrian Novialdi; Kaminudin Telaumbanua (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to find out systematically, factually and accurately about certain population facts or try to describe the phenomenon in detail. Collecting data used literature study by looking for theoretical references that are relevant to the effectiveness of group counseling services with role playing techniques in increasing students' social interactions. Data analysis technique is to use descriptive analysis method is done by compiling the data and facts obtained and then analyzed so as to provide the information needed. The results obtained from this study are group counseling services with role playing techniques are effective in increasing students' social interactions.